2007
DOI: 10.1002/ajmg.a.31766
|View full text |Cite
|
Sign up to set email alerts
|

Colobomatous macrophthalmia with microcornea syndrome maps to the 2p23‐p16 region

Abstract: Colobomatous macrophthalmia with microcornea syndrome (OMIM 602499) is a rare, autosomal dominant malformation characterized by microcornea, uveal coloboma, axial enlargement of the globe, and myopia. Using what is currently the largest described pedigree and candidate localization approach, we first excluded the candidate genes PAX2, PAX3, PAX6, and PAX9. Subsequently, the chromosome 14q24 region containing the CHX10, SIX1, and SIX4 genes were also excluded. Positive LOD scores were obtained with the DNA mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the same family, Elcioglu et al performed linkage analysis and identified the maximum possible LOD score of 3.61 in a candidate region on chromosome 2. Consistent with the large number of family members included in the linkage analysis, the probability of producing an LOD score of 3.61 by chance is very low (P ≤ 0.0001) (6). We therefore focused the search for the causative gene on this region, but we could not identify any candidate mutation after the initial analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the same family, Elcioglu et al performed linkage analysis and identified the maximum possible LOD score of 3.61 in a candidate region on chromosome 2. Consistent with the large number of family members included in the linkage analysis, the probability of producing an LOD score of 3.61 by chance is very low (P ≤ 0.0001) (6). We therefore focused the search for the causative gene on this region, but we could not identify any candidate mutation after the initial analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The number of animal studies investigating mechanisms of inherited eye disorders was also limited (Yaylacioglu Tuncay & Dincer, 2019). There have been relatively fewer studies investigating the genotype–phenotype correlations in inherited eye diseases from Turkey (Bardak et al, 2016; Ergun, Akay, Ergun, & Perçin, 2017; Karti et al, 2017; Semerci et al, 2014; Yaylacioglu Tuncay et al, 2016), and the most of these publications were accomplished by international collaborations (Bagiyeva et al, 2007; Elcioglu et al, 2007; Holt et al, 2017; Ozgul et al, 2004; Yamada et al, 2004) or by including Turkish patients living abroad (Angius et al, 2018; Iftikhar et al, 2019; Pach, Kohl, Gekeler, & Zobor, 2013). The dataset should grow about the genotypes of patients living in Turkey.…”
Section: Inherited Eye Diseases In Turkeymentioning
confidence: 99%